2018
DOI: 10.17129/botsci.1869
|View full text |Cite
|
Sign up to set email alerts
|

Host affinity and vertical distribution of epiphytic orchids in a montane cloud forest in southern Mexico

Abstract: <p class="Standard1"><strong>Background</strong>: The host´s structural characteristics provide diverse microhabitats that influence the distribution patterns of the epiphytes at different vertical zones and among tree species.</p><p class="Standard1"><strong>Hypotheses</strong>: Epiphytic orchids have preference for larger host trees and with non-exfoliating rough bark, while the limiting hosts will be those of smaller size and smooth and exfoliating bark, and there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
(100 reference statements)
2
7
0
4
Order By: Relevance
“…with fissured and slightly fissured bark, respectively, favored early emergence of new roots and longer root length. These observations are in agreement with the research by Hernández-Pérez et al (2018) in which a higher wealth and abundance of orchids was found in 23 species of fissured-bark trees and a lower wealth in 12 species of smoothbark trees. Similarly, Alzate-Q et al (2019) found that the phorophyte Clethra macrophylla presented a higher richness of epiphytic species (41%) related to its multiple branches and rough bark.…”
Section: Resultssupporting
confidence: 93%
“…with fissured and slightly fissured bark, respectively, favored early emergence of new roots and longer root length. These observations are in agreement with the research by Hernández-Pérez et al (2018) in which a higher wealth and abundance of orchids was found in 23 species of fissured-bark trees and a lower wealth in 12 species of smoothbark trees. Similarly, Alzate-Q et al (2019) found that the phorophyte Clethra macrophylla presented a higher richness of epiphytic species (41%) related to its multiple branches and rough bark.…”
Section: Resultssupporting
confidence: 93%
“…Zotz & Vollrath (2003) afirmam que a ocupação epifítica, assim como, a abundância por forófito, correlacionam-se axiomaticamente, com a idade da árvore e área do substrato. Existindo assim, uma especificidade entre orquídeas e altura e diâmetro do forófito (Hernández-Pérez et al 2018). À medida que as árvores crescem, tanto em diâmetro, quanto em altura, contribuem para mudanças na estrutura da sinúsia epifítica, aumentando a heterogeneidade de micro-hábitats, especialmente, dentro das copas (Woods et al 2015).…”
Section: Características De Forófitos E Não Forófitosunclassified
“…Esta espécie também foi verificada colonizando caule (colmo) de taquaras, em locais adjacentes a área de estudo. Estas variações de abundância, na estratificação vertical, ou preferências por zonas do forófito são, comumente, evidenciadas em outros estudos sobre epífitos (Zimmerman & Olmestd 1992;Rogalski & Zanin 2003;Kersten & Silva 2001;Hernández-Pérez et al 2018).…”
Section: Relações Entre Orquídeas E Forófitosunclassified
See 2 more Smart Citations